Pregunta
upstudy study bank question image url

O Radicals and Quadratic Functions Solving a radical equation with a quadratic expression under the radical Solve for \( x \), where \( x \) is a real number. \[ x=\sqrt{x^{2}+x+6} \] If there is more than one solution, separate them with commas. If there is no solution, click on "No solution".

Ask by Haynes Edwards. in the United States
Feb 02,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

There is no real solution to the equation \( x = \sqrt{x^{2} + x + 6} \).

Solución

To solve the equation: \[ x = \sqrt{x^{2} + x + 6} \] **Step 1: Determine the Domain** The square root is defined only when the expression inside is non-negative: \[ x^{2} + x + 6 \geq 0 \] The quadratic \( x^{2} + x + 6 \) has a discriminant: \[ \Delta = 1^2 - 4 \cdot 1 \cdot 6 = 1 - 24 = -23 \] Since the discriminant is negative, \( x^{2} + x + 6 \) is always positive for all real numbers \( x \). Additionally, since the square root yields a non-negative value, \( x \) must satisfy: \[ x \geq 0 \] **Step 2: Square Both Sides** \[ x^2 = x^{2} + x + 6 \] Subtract \( x^2 \) from both sides: \[ 0 = x + 6 \implies x = -6 \] **Step 3: Check for Extraneous Solutions** The potential solution \( x = -6 \) does not satisfy the domain condition \( x \geq 0 \). Additionally, substituting \( x = -6 \) back into the original equation: \[ -6 = \sqrt{(-6)^2 + (-6) + 6} \implies -6 = \sqrt{36} \implies -6 = 6 \] This is a contradiction. **Conclusion** There are no real solutions to the equation. **Answer:** No solution

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the equation \( x=\sqrt{x^{2}+x+6} \), we first square both sides to eliminate the square root: \[ x^2 = x^{2} + x + 6 \] Now, rearranging gives us: \[ 0 = x + 6 \] This simplifies to \( x = -6 \). To ensure this is a valid solution, we substitute back into the original equation: \[ -6 = \sqrt{(-6)^{2} + (-6) + 6} \] Calculating inside the square root: \[ = \sqrt{36 - 6 + 6} = \sqrt{36} = 6 \] Clearly, \(-6 \neq 6\). So, this does not hold. Thus, there is no real solution to the equation. **Final Answer: No solution.**

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad